STUDI PENANGGULANGAN LIMBAH MERKURI DAMPAK AKTIVITAS PERTAMBANGAN EMAS TERHADAP LINGKUNGAN DAN KESEHATAN MASYARAKAT SEKITAR - Nurjanah, Siti; Rifandi, Raditya Ahmad; Ulfiyanti, Ulfiyanti (Jounal of Enviromental Science Sustainable, 2024)
Mercury waste is produced from various sources because mercury is used in several types of products and processes, and is also contained in minerals such as coal. This research aims to assess the potential impact of mercury pollution on the environment. The elimination of mercury in products and processes along with strict controls on mercury emissions and releases in response to the Minamata Convention is a worrying increase in the production of mercury waste which requires environmentally sound management (ESM). Then this research uses the literature review method in 20 journals consisting of 10 national journals and 10 international journals related to handling mercury pollution in waters and sediments from mining activities, then there are several discussions based on mercury waste in gold mining results for the community and surrounding natural environment. The majority have conclusions regarding mercury waste in gold mines regarding public health.